In Vitro Response of Protocorm Grammatophyllum stapeliiflorum (Teijsm. & Binn.) J.J.Sm. Orchid in Growth on Several Media Composition - Ranny Wirmasari; Mayta Novaliza Isda (Universitas Andalas, 2019)
Family Orchidaceae has about 800 genera which are already difficult to find and almost extinct, including the orchid genus Grammatophyllum. A species of rare orchids, Grammatophyllum stapeliiflorum, is hard to find in original habitat. The addition of Growmore, BAP and 15% coconut water is expected to increase the growth and development of the G. stapeliiflorum orchid protocorms. This study use a Completely Randomized Design, consisting of 6 treatments (control, 1 and 3 mg/l BAP, 1 and 3 g/l Growmore, and 150 ml/l coconut water) in MS media with 5 replicates with observation for 4 weeks after planting. The results showed did not differ markedly in the number of protocorms, number of shoots and number of browning protocorms, but differ markedly in the parameter protocorm color based on DMRT test. Treatment of 3 mg/l BAP gives the best results on the number of shoots 2,60 protocorms and number of browning protocormss at the least amount 0,80 protocorms. The number of protocorms most widely on the treatment of 1 g/l Growmore 14,40 protocorms. Protocorms color is best found in 3 g/l Growmore with green color. This research managed to multiply the number of protocorms and induces protocorms shoots from Grammatophyllum stapeliiflorum orchid.